Evaluation Of Sediment Size For Flow Estimation In Alluvial Channel - Lee, Wai Hong (2013)
Flow estimation in alluvial channel is one of the most common practices in river engineering. A lot of methods are introduced in water resources field towards increasing the accuracy of determining the roughness coefficient as well as estimating the flow based on sediment size. However, most of these studies are mainly based on idealized laboratory conditions such as uniform flow and uniform sedimentation. These derived methods do not satisfy for channel with irregular shapes. The interest of this study is to determine the roughness coefficient in term of choices of sediment size towards non uniform sedimentation distribution in irregular channel. A few relevant well known equations are used in evaluating and comparing the flow resistance estimation. In this study, a total number of 167 sets of field data were collected. 31 sets data which collected from Sungai Jawi were used to investigate the hydraulic characteristics of Sungai Jawi. Another 143 sets field data of eight selected rivers collected from previous studies were used to evaluate the accuracy of existing well known equations for determining the flow resistance. Throughout the analysis, none of the method estimates the flow accurately. Sediment mode size, d65, was proposed to represent the sediment mixture for flow estimation purpose. At the end of this study, an equation had been developed based on the total 167 sets of data. This equation is intended to determine the flow resistance with the ratio of hydraulic radius and averaged flow depth to the sediment mode size. The results show an improvement to the discrepancy of flow estimation based on the applicable d65.